2015
DOI: 10.1071/mf14134
|View full text |Cite
|
Sign up to set email alerts
|

Re-evaluation of the diversity and distribution of diazotrophs in the South China Sea by pyrosequencing the nifH gene

Abstract: Abstract. Previous studies on the diversity and composition of nifH genes in the South China Sea (SCS) were mainly based on quantitative PCR and DNA clone methods. The pyrosequencing results of partial nifH gene fragments were used to study the spatiotemporal heterogeneity in composition and diversity of diazotrophs in the SCS. Seawater samples were collected throughout the upper ocean (,200-m depth) in different sites, as follows: the Pearl River Estuary; Taiwan and Luzon Straits (which are affected by the Ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…A previous study indicated that Gamma A can be preferentially amplified in PCR libraries (Turk et al ). Amplification bias may have caused the role of UCYN‐B in the western Pacific to be ignored in previous studies that used clone libraries or high‐throughput sequencing (Moisander et al ; Zhang et al ; Xiao et al ; Shiozaki et al ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study indicated that Gamma A can be preferentially amplified in PCR libraries (Turk et al ). Amplification bias may have caused the role of UCYN‐B in the western Pacific to be ignored in previous studies that used clone libraries or high‐throughput sequencing (Moisander et al ; Zhang et al ; Xiao et al ; Shiozaki et al ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the (sub)tropical South China Sea (SCS) is a semienclosed basin. Although previous studies indicated that Trichodesmium and proteobacterial groups were the two dominant nifH phylogenetic groups in the SCS, NFRs and activity of major diazotrophic groups are still unknown (Moisander et al ; Kong et al ; Zhang et al ; Xiao et al ). The Philippine Sea is almost entirely surrounded by island arcs (Uyeda and Ben‐Avraham ).…”
mentioning
confidence: 98%
“…In recent years, nifH amplicon sequencing using next generation sequencing technologies have greatly increased the number of nifH sequences (e.g. Farnelid et al 2011, Bentzon-Tilia et al 2015, Messer et al 2015, Turk-Kubo et al 2015, Xiao et al 2015, Cheung et al 2016. Compared to traditional clone library studies, sublineages present at low abundances are more likely to be recovered using next generation sequencing, which aids our efforts to describe novel UCYN-A sublineages.…”
Section: Increasing Amounts Of Ucyn-a Nifh Sequences Reveal Novel Submentioning
confidence: 99%
“…As of May 2015, over a decade after the discovery of UCYN-A, less than 1000 UCYN-A nifH sequences had been deposited to the National Center for Biotechnology Information (NCBI) GenBank database. Studies that have used next-generation sequencing (NGS) technologies on nifH gene fragments amplified using degenerate nifH primers have also recently reported UCYN-A sequences (Farnelid et al 2011, Bentzon-Tilia et al 2015, Messer et al 2015a,b, Turk-Kubo et al 2015, Xiao et al 2015, Doblin et al 2016. The greater depth of sequence coverage in these studies, compared to traditional clone libraries, may have favored its recovery in unexpected environments such as the Danish Strait (Bentzon-Tilia et al 2015) and an inverse hypersaline estuary in the South Australian Bight (Messer et al 2015a).…”
mentioning
confidence: 99%